Transcendental imaging and augmented reality. Issue 1 (5th September 2011) - Stott, Peter
Man has built tools to extend his visual experience in order to explore reality beyond his sensory capacity, for example microscopes, telescopes, high shutter speed and infrared cameras. However he has yet to build a visual tool to fully explore visual realms beyond his ordinary cognitive faculties. With the development of computing, comes the possibility of creating a tool to explore the virtual forms/spaces of images that are ordinarily inaccessible. This article identifies how cognition is ordinarily limited and posits a way of going beyond those limits, by defining a computational model of how those virtual spaces might be explored. This definition is based on brief but repeated empirical experiences of 'higher order' manifestations.